Circadian clock genes Bmal1 and Period may regulate nocturnal spawning by controlling sex hormone secretion in razor clam Sinonovacula constricta - Liu, Yanzi; He, Qinyuan; Yao, Hanhan; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2022)
The circadian clock is an endogenous regulation mechanism that coordinates biological processes with daily changes, which are regulated by circadian clock genes. Bmal1 and Period are key circadian clock genes and their roles in reproductive development have been widely studied. The spawning time of Sinonovacula constricta is limited to the night even under external artificial stimulation, and it might be regulated by the internal circadian clock. In this study, the heart rate of S. constricta was higher between 20:00-04:00 at night and lower between 12:00-16:00 during the day, and the sex hormone contents were the highest at 00:00 and the lowest at 18:00 (P < 0.01). Therefore, these obvious changes in the circadian rhythm indicate that S. constricta is a nocturnal animal. The open reading frame (ORF) of Bmal1 comprises 1944 bp encoding 647 aa, while the ORF of Period comprises 3111 bp encoding 1036 aa. Bmal1 and Period were both expressed in four tissues, but they had opposite rhythmic expression patterns. Bmal1 expression was higher at 00:00-06:00 and lower at 12:00-18:00, and Period expression was opposite, thereby suggesting that Bmal1 and Period are involved in positive and negative pathways regulated by the circadian clock, respectively. Strong protein fluorescence signals of Bmal1 and Period proteins were observed in mature oocytes, spermatids, hepatocytes, and epithelial cells of siphons. After siRNA interference, the expression of both Bmal1 and Period significantly decreased (P < 0.01), and the sex hormone contents decreased significantly from 3 to 7 days in the siRNA treatment groups (P < 0.01). Therefore Bmal1 and Period may regulate nocturnal spawning by controlling sex hormone secretion. These findings provide a theoretical basis for understanding the molecular mechanism related to spawning, and may facilitate the artificial propagation of mollusks.